2016
DOI: 10.1111/desc.12401
|View full text |Cite|
|
Sign up to set email alerts
|

Longitudinal development of manual motor ability in autism spectrum disorder from childhood to mid‐adulthood relates to adaptive daily living skills

Abstract: Many individuals with autism spectrum disorder (ASD) exhibit motor difficulties, but it is unknown whether manual motor skills improve, plateau, or decline in ASD in the transition from childhood into adulthood. Atypical development of manual motor skills could impact the ability to learn and perform daily activities across the life span. This study examined longitudinal grip strength and finger tapping development in individuals with ASD (n=90) compared to individuals with typical development (n=56), ages fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
71
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 72 publications
8
71
2
2
Order By: Relevance
“…Precisely 49 studies comparing ASC and typically-developing (TD) control groups answer this question in the affirmative. The more methodologically rigorous studies, those which a) either matched for chronological and/or mental age and/or IQ or b) controlled for these in their analyses, and c) had more sizeable groups (>30 per group) demonstrate that motor impairments occur more often than might be expected in TD children (AbuDahab, Skidmore, Holm, Rogers, & Minshew, 2013;Ament et al, 2015;Dewey, Cantell, & Crawford, 2007;Dowell, Mahone, & Mostofsky, 2009;Duffield et al, 2013;Dziuk et al, 2007;Floris et al, 2016;Sumner, Leonard, & Hill, 2016;Travers et al, 2015Travers et al, , 2016. A meta-analysis of 41 studies confirmed that, despite substantial variation, effect sizes are large with TD participants significantly outperforming individuals with autism in motor coordination, arm movements, gait and postural stability (Fournier, Hass, Naik, Lodha, & Cauraugh, 2010), and that these effects did not seem affected by publication bias.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Precisely 49 studies comparing ASC and typically-developing (TD) control groups answer this question in the affirmative. The more methodologically rigorous studies, those which a) either matched for chronological and/or mental age and/or IQ or b) controlled for these in their analyses, and c) had more sizeable groups (>30 per group) demonstrate that motor impairments occur more often than might be expected in TD children (AbuDahab, Skidmore, Holm, Rogers, & Minshew, 2013;Ament et al, 2015;Dewey, Cantell, & Crawford, 2007;Dowell, Mahone, & Mostofsky, 2009;Duffield et al, 2013;Dziuk et al, 2007;Floris et al, 2016;Sumner, Leonard, & Hill, 2016;Travers et al, 2015Travers et al, , 2016. A meta-analysis of 41 studies confirmed that, despite substantial variation, effect sizes are large with TD participants significantly outperforming individuals with autism in motor coordination, arm movements, gait and postural stability (Fournier, Hass, Naik, Lodha, & Cauraugh, 2010), and that these effects did not seem affected by publication bias.…”
mentioning
confidence: 99%
“…Other studies of kinematics in very basic arm movements and reaching and grasping reveal differences between autistic and TD participants (Campione, Piazza, Villa, & Molteni, 2016;Cook, Blakemore, & Press, 2013). Use of more traditional neuropsychological tests reflect poorer performance in the grip strength (Abu-Dahab et al, 2013;Hardan et al, 2003;Travers et al, 2015Travers et al, , 2016, finger tapping (Abu-Dahab et al, 2013;Duffield et al, 2013;Hardan et al, 2003;Travers et al, 2016) and pegboard tasks (Abu-Dahab et al, 2013;Ament et al, 2015;Barbeau, Meilleur, Zeffiro, & Mottron, 2015;Duffield et al, 2013;Hardan et al, 2003). These tests ascend in difficulty, primarily testing muscle strength, simple motor coordination and dexterity respectively.…”
mentioning
confidence: 99%
See 3 more Smart Citations